Brewpitopes: a pipeline to refine B-cell epitope predictions during public health emergencies - Farriol-Duran, Roc; López-Aladid, Ruben; Porta-Pardo, Eduard; Torres, Antoni; Fernández-Barat, Laia (Frontiers in Immunology, 2023)
The application of B-cell epitope identification to develop therapeutic antibodies and vaccine candidates is well established. However, the validation of epitopes is highly consuming in terms of time and experimental resources. To alleviate this, in recent years multiple computational predictors have been developed in the immunoinformatics community. Brewpitopes is a pipeline to curate bioinformatic B-cell epitope predictions obtained integrating different state-of-the-art tools. We used additional computational predictors to account for subcellular location, glycosylation status and surface accessibility of the predicted epitopes. The implementation of these set of rational filters optimizes in vivo antibody recognition properties of the candidate epitopes. To validate Brewpitopes, we performed a proteome-wide analysis of SARS-CoV-2 with a particular focus to S protein and its Variants of Concern. In the S protein, we obtained a 5-fold enrichment in terms of predicted neutralization versus the epitopes identified by individual tools. We analyzed epitope landscape changes caused by mutations in the S protein of new viral variants was linked to observed immune escape evidence in specific strains. In addition, we identified a set of epitopes with neutralizing potential in 4 SARS-CoV-2 proteins (R1AB, R1A, AP3A and ORF9C). These epitopes and antigenic proteins are conserved targets for viral neutralization studies. In summary, Brewpitopes is a powerful pipeline to refine B-cell epitope bioinformatic predictions during public health emergencies in a high-throughput capacity to facilitate the optimization of experimental validation of therapeutic antibodies and candidate vaccines.